Modernization of Ayurveda: A Needful or Purposeless Task - Suhas M; Shreevathsa B M (RGUHS Journal of AYUSH Sciences)
The valuable knowledge of ancient India initially was passed down from gurus to their shishyas in the form of oral narration Shruti and this was later transferred in the form of writings Smruti due to various limitations. Ayurveda existed as the Upaveda of Atharva Veda. This ancient medical science has traversed through various time periods until today. With the advancement of contemporary sciences there are consequential discussions among the Ayurveda fraternity with regards to the necessity for modernization of Ayurveda. It is need of the moment to assess and reassess the need for modernization of Ayurveda. The present study was one such attempt oriented towards elucidating ldquoModernizationrdquo in the field of Ayurveda and determine the domains that demand modernization and those that do not need it. The classical texts of Ayurveda and research articles from standard e-data base were consulted for the study. Initially the guidelines for upgradation of Ayurveda provided in the classicals were investigated. Later published research articles were reviewed for the gap-analysis. Finally domains that demand modernization and those that does not yield an outcome were delineated. It was found that acharyas have provided an internal framework within which Ayurveda can be modernized. All these principles fall into either lsquoStaticrsquo domain or lsquoDynamicrsquo domain among which only those under dynamic domain demand timely modernization. To conclude for a shastra to be alive for ages the practice of its core principles is most essential. But when the practice needs modifications without opposing the authenticity there is no harm in accepting the same.